Antibody-independent and dependent infection of human myeloid cells with dengue virus is inhibited by carrageenan - Piccini, Luana Érica (2020)
This study demonstrated that the λ-carrageenan is a potent and selective inhibitor of the primary infection of human myeloid U937 and K562 cells with the four DENV serotypes, achieving a higher than 99 % reduction in virus production at the highest tested concentration of 20 μg/mL, without affecting cell viability at concentrations up to 1000 μg/mL. Since antibody-dependent enhancement (ADE) is thought to play a main role in the aggravation of severe DENV disease, we also evaluated the activity of carrageenan against ADE of DENV infection. The λ-carrageenan was also effective to block the antibody dependent infection mediated by Fcγ-RII in both cell lines, causing 96–99 % inhibition in virus production from cells infected with immune complexes of DENV-2 and DENV-3. Moreover, the inhibitory effectiveness of carrageenan was similar against prM-mediated ADE or E-mediated ADE. Mechanistic studies indicated that DENV-2 entry is the main antiviral target for carrageenan in DENV or DENV-Ab infected human myeloid cells since a strong inhibitory effect was observed when the carrageenan was present only during adsorption at 4 °C or internalization at 37 °C, whereas the infection was not altered when the compound was added after virus internalization. Thus, our findings have shown that carrageenan may be considered an interesting antiviral agent able to block DENV entry during both primary and antibody-dependent infection of human myeloid cells.